1995
DOI: 10.1083/jcb.128.6.1081
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin NH2-terminal domain inhibits the cell extension activity of the COOH-terminal domain.

Abstract: Abstract. Overexpression in insect cells of the full coding sequence of the human membrane cytoskeletal linker ezrin (1-586) was compared with that of a NHEterminal domain (ezrin 1-233) and that of a COOHterminal domain (ezrin 310-586). Ezrin (1-586), as well as ezrin (1-233) enhanced cell adhesion of infected Si x ) cells without inducing gross morphological changes in the cell structure. Ezrin (310-586) enhanced cell adhesion and elicited membrane spreading followed by microspike and lamellipodia extensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
113
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 49 publications
9
113
0
Order By: Relevance
“…A number of studies have utilized the N-ERMAD of ERM proteins as dominant inhibitory constructs and demonstrated that the introduction of this domain alone can alter the function of endogenous ERM proteins, but the molecular mechanism whereby the N-ERMAD achieves dominant inhibition is hitherto poorly understood (Martin et al, 1995;Crepaldi et al, 1997;Amieva et al, 1999). The N-ERMAD can either bind to receptors or scaffolding proteins at the plasma membrane, and thus abrogate binding of endogenous ERM proteins, or interacts directly with the C-ERMAD and thus altering the actin-binding capacities of endogenous ERM proteins.…”
Section: Mutation Of Glutamic Acid 244 In the N-ermad Of Ezrin Decreamentioning
confidence: 99%
“…A number of studies have utilized the N-ERMAD of ERM proteins as dominant inhibitory constructs and demonstrated that the introduction of this domain alone can alter the function of endogenous ERM proteins, but the molecular mechanism whereby the N-ERMAD achieves dominant inhibition is hitherto poorly understood (Martin et al, 1995;Crepaldi et al, 1997;Amieva et al, 1999). The N-ERMAD can either bind to receptors or scaffolding proteins at the plasma membrane, and thus abrogate binding of endogenous ERM proteins, or interacts directly with the C-ERMAD and thus altering the actin-binding capacities of endogenous ERM proteins.…”
Section: Mutation Of Glutamic Acid 244 In the N-ermad Of Ezrin Decreamentioning
confidence: 99%
“…The N-terminal domain of ezrin, when expressed in mammalian cells, locates to the plasma membrane, whereas the C-terminal domain is enriched in the actin cytoskeleton [5], possibly via a recently identified actin binding site in that region [6]. Overexpressed intact ezrin accumulates at the plasma membrane of insect cells [7], and overexpression of the C-terminal site in these cells induces formation of cell extensions [8]. Interestingly, the N-terminal domain inhibits the latter effect [8].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpressed intact ezrin accumulates at the plasma membrane of insect cells [7], and overexpression of the C-terminal site in these cells induces formation of cell extensions [8]. Interestingly, the N-terminal domain inhibits the latter effect [8]. Recently, the presence of two self-associating domains in ezrin, termed N-and C-ERMADs (ezrin-radixinmoesin association domains) has been demonstrated [9].…”
Section: Introductionmentioning
confidence: 99%
“…The N-termini of radixin and ezrin can exert a regulatory in¯uence over their C-termini either in cis or in trans Martin et al, 1995) via an intramolecular association (Gary and Bretscher, 1995;Magendantz et al, 1995). We tested whether such interactions are required for the growth inhibiting functions of merlin by stably transfecting RT4-D6P2T cells with both NF2-N and NF2-C17 using di erent selectable markers.…”
mentioning
confidence: 99%